2019
DOI: 10.1101/2019.12.13.876128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution and strength of interlaminar synaptic connectivity in mouse primary visual cortex revealed by two-photon optogenetic stimulation

Abstract: The most common synaptic connections between neurons in different cortical layers form the basis of the canonical cortical microcircuit. Understanding of cortical function will require further development and application of methods to efficiently characterize synaptic connections within and outside of the canonical pathway. Accordingly, we measured synaptic inputs onto superficial excitatory neurons in response to sequential two-photon optogenetic stimulation of neurons in deeper layers. Layer 4 excitatory neu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Here we demonstrated that the Ai203 reporter line can be used to rapidly map synaptic connectivity by recording postsynaptic currents while performing 2p stimulation. Prior 2p mapping experiments used either viral tools that result in opsin expression variability within and across animals, or transgenic lines that do not have soma-targeted expression of opsins (Baker et al, 2016;Hage et al, 2019;Karnani, Jackson, Ayzenshtat, Sichani, et al, 2016;Karnani, Jackson, Ayzenshtat, Tucciarone, et al, 2016;Naka et al, 2019;Packer et al, 2012;Shemesh et al, 2017). The Ai203 reporter line combines the advantages of soma-targeting with the convenience of transgenic expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we demonstrated that the Ai203 reporter line can be used to rapidly map synaptic connectivity by recording postsynaptic currents while performing 2p stimulation. Prior 2p mapping experiments used either viral tools that result in opsin expression variability within and across animals, or transgenic lines that do not have soma-targeted expression of opsins (Baker et al, 2016;Hage et al, 2019;Karnani, Jackson, Ayzenshtat, Sichani, et al, 2016;Karnani, Jackson, Ayzenshtat, Tucciarone, et al, 2016;Naka et al, 2019;Packer et al, 2012;Shemesh et al, 2017). The Ai203 reporter line combines the advantages of soma-targeting with the convenience of transgenic expression.…”
Section: Discussionmentioning
confidence: 99%
“…Data are presented as mean ± sem. 2p Synaptic Connectivity Mapping Finally, we tested the use of Ai203 in in vitro synaptic connectivity mapping by using 2p optogenetics to rapidly identify putative monosynaptic connections to a neuron of interest (Baker et al, 2016;Hage et al, 2019;Karnani, Jackson, Ayzenshtat, Sichani, et al, 2016;Karnani, Jackson, Ayzenshtat, Tucciarone, et al, 2016;Naka et al, 2019;Packer et al, 2012;Shemesh et al, 2017). We first measured the effective spatial resolution of photostimulation by recording spiking in an opsin-positive L2/3 pyramidal neuron while stimulating each point in a smaller 3D grid surrounding the cell (Fig.…”
Section: F)mentioning
confidence: 99%
See 1 more Smart Citation
“…However connections across distant layers are more difficult to interrogate with this method because long axo-dendritic pathways are more likely to be severed (Stepanyants et al, 2009), especially in human cortical tissue that can be several millimeters from pia to white matter. A detailed study of such medium-range connections may require a different methodological approach (Hage et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…Our experiments also revealed strong mutual inhibition among SOM cells, and relatively weak inhibition among PV cells ( Figure 5 ). These results are surprising for two reasons: recent studies on mutual inhibition between interneuron subtypes have shown that SOM cells inhibit most other interneuron subtypes while avoiding inhibiting one another (but see ref 44 ); and PV cells exhibit the opposite connectivity patterns, strongly inhibiting other PV interneurons while making few connections to other genetically distinct interneurons 45 .…”
Section: Discussionmentioning
confidence: 99%